Deskripsi perilaku kemalasan sosial siswa dan implikasinya terhadap layanan bimbingan dan konseling - Aritosmen, Fharid; Daharnis, Daharnis (Universitas Negeri Padang, 2023)
Groups are an integral part of students' daily lives, and activities carried out in groups can make students into individuals who have the ability to interact, communicate, and work together to achieve the same goals. However, in reality, there are still students who reduce their efforts to be involved in group activities. This reduced effort is an individual's tendency to engage in social loafing or social laziness. This study aims to describe students' social loafing behavior in several aspects: (1) motivation, (2) activity, (3) responsibility, (4) dompleng (a free ride), and (5) responses to evaluations from other people. This study uses a quantitative descriptive method. The population in this study was 645 students in grades XI and XII at SMAN 16 Padang for the 2021/2022 academic year and a sample of 250 students. sampling technique using proportional random sampling. The collection of data for this study used a behavioral questionnaire on social loafing in students of SMAN 16 Padang. The results of this study indicate that the social loafing behavior of SMAN 16 Padang students is in the moderate category. The results of research on the social loafing behavior of students at SMAN 16 Padang can be seen in detail as follows: (1) The social loafing behavior of students seen from the motivational aspect is in the low category; (2) students' social loafing behavior seen from the aspect of liveliness is in the medium category; (3) students' social loafing behavior seen from the aspect of responsibility is in the medium category; (4) students' social loafing behavior seen from the dompleng aspect is in the medium category; and (5) students' social loafing behavior seen from the aspect of the response to the evaluation is in the medium category.